PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE PADA MATERI SEGI EMPAT - Pesik, Anekke; Sulistyaningsih, Murni; Kandouw, Prilly (Universitas Negeri Manado, 2020)
ABSTRACT. This research was conducted to examine the average student learning outcomes on rectangular or quadriteral after being taught by using the cooperative learning model ofo think pair square and the average student learning outcomes after being taught by using the direct learning model on rectangular learning. This research is experimental research. The sample in this study is class VII-A as an experimental class and VII-B as a control class in SMP Negeri 2 Kakas in the academic year 2019/2020. The instrument used in this study was the test results of the quadrilateral learning material in the form of question matter. Data collection techniques are through the posttest in the experimental class and the control class. The results of the study concluded that the average learning outcomes of students who were taught using the cooperative learning model think pair square more than the average learning outcomes of students who were taught using the direct learning model.Â Â Keywords: Mathematics Learning Outcomes, Cooperative Think Pair Square Type, Quadrilateral